Temperature Effects on Growth and Culture Stability of Chlorella sp. in Laboratory Cultivation - Anggraini, Winda Trisna; Santoso, Ruth Suci Wadini; Saputri, Wulandari Prasetya; Prakoso, Nurcahyo Iman; Utami, Maisari; Sasongko, Setyo Yanus; Purwiandono, Gani (Chemistry Department, Universitas Islam Indonesia, 2026)
The growth behavior of chlorella sp. was evaluated under different temperature conditions to examine how thermal variation influences microalgal biomass production and culture dynamics. Cultivation experiments were conducted at 28, 35, and 40°C under continuous illumination with aeration. Biomass accumulation was monitored through optical density measurements at 680 nm, while physicochemical parameters including pH and total dissolved solids (TDS) were recorded throughout cultivation. Stable biomass accumulation was observed at 28°C, whereas growth became less consistent at 35°C and declined at 40°C, indicating increasing thermal stress at higher temperatures. Variations in pH and TDS during cultivation supported the observed temperature-dependent metabolic response. The analytical workflow used to monitor microalgal growth was further evaluated using the AGREE metric based on the principles of Green Analytical Chemistry. The estimated AGREE score of approximately 0.76 indicates a moderately green analytical procedure. The results highlight the importance of temperature control in maintaining stable microalgal cultivation and demonstrate the potential of integrating environmental performance assessment into microalgal growth studies.